Responsive Adjudication and the 'Social Legitimacy' of the Internal Market. Issue 5 (September 2016) - Mulder, Jotte
Abstract: This article is concerned with the social legitimacy of EU free movement adjudication. What does social legitimacy entail within the multi‐level 'embedded liberalism' construction of the internal market? How can the objective of free movement (market access) and a commitment to social diversity both be pursued without one necessarily trumping the other? This article seeks to contribute to these questions on the basis of a discussion of what has come to be known as the argument from transnational effects and the development of an adjudicative model that can be termed 'socially responsive'. On the basis of an 'ideal types' analysis of the case law of the Court, it is concluded that responsiveness to Member State social context is lacking in any coherent form in the case law of the Court of Justice of the European Union. However, a responsive model of adjudication can be (re)constructed by streamlining the identified ideal type adjudicative rationales. In the midst of this process of discovery, an operational rationale to establish the substantive (social) scope and reach of the internal market shall be submitted.